THE PANEVEZYS–SALDUTISKIS RAILWAY CASE IN THE DIARIES OF M. RÖMERIS - Ieva Deviatnikovaitė (Jurisprudencija, 2022)
Mykolas Römeris wrote about various legal issues in his diaries. He also wrote about cases that were examined at the Permanent Court of International Justice in The Hague, where the prominent Lithuanian lawyer served as an ad hoc judge (or national Lithuanian judge). He wrote about the case of the interpretation of the Statute of the Memel Territory, to which he devoted numerous pages in volume 34 of his diaries. Naturally, he also wrote about the case of the Panevėžys–Saldutiškis railway, to which this article is dedicated. While describing the Panevėžys–Saldutiškis case in his diaries, Römeris: looked into issues of international law and the process of hearing cases at the Permanent Court of International Justice; analyzed the ad hoc role of the judge and not only the legal, but also the political and psychological reasons for making decisions; described in detail the judges’ discussions, considering one or another issue, the origin of the case, the legal intricacies of the case, the Lithuanian delegation, the preparation of Lithuania’s defense strategy, and preparation for the judicial process; and presented his opinion regarding the preliminary objections presented by Lithuania. The structure of this article was determined by the progress and stages of the trial process. The scientific foundation of this research consists of the material of two funds stored in the Wróblewski Library of the Lithuanian Academy of Sciences, Vilnius University Library. The historical, comparative, analytical, descriptive, linguistic, and document analysis methods were used in the research.